Whole‐body MR angiography: First experiences with the new TimCT technology with single contrast injection. Issue 2 (16th May 2013) - Naguib, Nagy N.N.; Bohrt, Kevin; Nour‐Eldin, Nour‐Eldin A.; Schulz, Boris; Tawfik, Ahmed M.; Siebenhandel, Petra; Bodelle, Boris; Eichler, Katrin; Moritz, Anton; Vogl, Thomas J.; Zangos, Stephan
<x xml:space="preserve">Abstract</x> Purpose To assess image quality, presence of artifacts, arterial stenosis, and interobserver agreement of Tim‐CT in assessment of the arterial system using contrast‐enhanced whole‐body‐MRA (CE‐Wb‐MRA) with a single contrast‐medium injection in patients with arteriosclerosis. Materials and Methods The retrospective study included 18 patients (mean age, 68 years). A total of 468 arteries were evaluated. CE‐Wb‐MRA was performed using Tim‐CT technology on a 1.5 Tesla (T) MRI after injecting a single dose of Vasovist. Evaluations were independently performed by two radiologists. The arterial system was divided into seven anatomic locations. Each radiologist assessed the image quality, degree of artifacts, and arterial stenosis in different locations. Results All Wb‐MRA examinations were technically successful. Image quality: 28.42% arteries were excellent, 29.17% were good, 22.54% were satisfactory, 9.40% were poor, and 5.13% of insufficient quality. Occurrence of artifacts: 37.25% were free of artifacts, 49.44% minimal artifacts not affecting diagnosis, and 13.31% strong artifacts not permitting a diagnosis. A total of 60.00% arteries showed no stenosis, 8.76% were ≤50% stenotic, 5.17% were 51–75% stenotic, 4.38% were 76–99%, and 8.54% total occlusion. The interobserver agreement was good for supra‐aortic, pelvic, and upper and lower leg regions. Conclusion CE‐Wb‐MRA using the TimCT technology and with a single contrast injection is a feasible tool for whole‐body MRA. J. Magn. Reson. Imaging 2014;39:434–439. © 2013 Wiley Periodicals, Inc.